Growth and Development Levels of 13 Year Old Children - Sudirman, Akbar; Hasbunallah, Hasbunallah; Bachtiar, Ishak; Mappaompo, M.Adam (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the profile of the level of growth and motor development of 13 year old male students in class VII at SMP Rama Sejahtera Makassar. Through this research, researchers can provide general information regarding the growth and motor development of 13 year old children who live in the middle of the city of Makassar, especially boys as the main focus that is accessible in this research. And the data from this research can be used by related parties, especially the Education Department, which collaborates with the Makassar City Health Service to carry out field reviews for the sake of continued growth and better development of children as future generations. The research method uses a quantitative descriptive approach by carrying out tests directly using test and measurement instruments. The sample in this study was 13 year old male students in class VII at SMP Rama Sejahtera Makassar totaling 30 people.